2011
DOI: 10.1038/npp.2011.218
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor in the Norepinephrine Nucleus, Locus Coeruleus, Facilitates Behavioral Flexibility

Abstract: Corticotropin-releasing factor (CRF), the stress-related neuropeptide, acts as a neurotransmitter in the brain norepinephrine nucleus, locus coeruleus (LC), to activate this system during stress. CRF shifts the mode of LC discharge from a phasic to a high tonic state that is thought to promote behavioral flexibility. To investigate this, the effects of CRF administered either intracerebroventricularly (30-300 ng, i.c.v.) or directly into the LC (intra-LC; 2-20 ng) were examined in a rat model of attentional se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 74 publications
10
93
1
1
Order By: Relevance
“…We estimated CRF concentrations at the LC following diffusion from the peri-LC infusion site using the upper bounds estimate (Newton's inverse square law) and with more realistic models that account for the diffusion coefficient of CRF, volume fraction, and tortuosity (Nicholson, 2001;Shorten and Wall, 2001). These analyses indicate that our peri-LC infusions resulted in CRF concentrations within the LC nucleus nearly identical to previous studies that directly infused CRF within the LC (Curtis et al, 1997;Snyder et al, 2012). Specifically, following 300 ng CRF infusions, maximal estimates of CRF were 30 and 3 ng at distances of 32 and 110 mm from the infusion needle, respectively, using the inverse square method.…”
Section: Technical Considerationssupporting
confidence: 81%
“…We estimated CRF concentrations at the LC following diffusion from the peri-LC infusion site using the upper bounds estimate (Newton's inverse square law) and with more realistic models that account for the diffusion coefficient of CRF, volume fraction, and tortuosity (Nicholson, 2001;Shorten and Wall, 2001). These analyses indicate that our peri-LC infusions resulted in CRF concentrations within the LC nucleus nearly identical to previous studies that directly infused CRF within the LC (Curtis et al, 1997;Snyder et al, 2012). Specifically, following 300 ng CRF infusions, maximal estimates of CRF were 30 and 3 ng at distances of 32 and 110 mm from the infusion needle, respectively, using the inverse square method.…”
Section: Technical Considerationssupporting
confidence: 81%
“…The ability of moderate levels of CRF in the DRN to facilitate strategy set-shifting in the present study is reminiscent of the improvement of attention set shifting by similar levels of CRF in the LC (Snyder et al, 2012). Together the results suggest that acute stress can facilitate this form of cognitive flexibility through parallel actions of CRF in the LC and DRN and this is an adaptive cognitive response to the stressor.…”
Section: Discussionsupporting
confidence: 71%
“…Graybeal et al [11] found that injection of brain-derived neurotrophic factor (BDNF) directly into the vmPFC following stress is sufficient to prevent facilitation of reversal learning. In addition, a high dose of corticotropin-releasing factor (CRF) injected into the locus coeruleus facilitates reversal learning in rats [27]. Stress-induced changes in neurotransmitters such as glutamate, dopamine, and serotonin may also play a role in reversal learning facilitation [14,15,28].…”
Section: Discussionmentioning
confidence: 99%